АDMINISTRATIVE AND LEGAL SUPPORT OF THE LEGAL REGIME OF MARTIAL LAW IN UKRAINE - Пашинський, В.; Ступак, Д. (Київський національний університет імені Тараса Шевченка, 2023)
The issue of administrative and legal support of the legal regime of martial law was considered. Scientific views on such legal categories as "legal provision" and "administrative-legal provision" in various spheres of social relations have been studied. The concept of "administrative and legal support of the legal regime of martial law" is considered. The key features of the administrative and legal support of the legal regime of martial law are established, namely: the support of the specified legal regime is carried out by special entities whose powers are defined by legislation; regulated by the norms of administrative law; implemented using special tools (mechanisms, measures); the activity of public administration subjects consists in the adoption of laws, subordinate regulatory legal acts and their implementation. Based on the results of the research, the author's definition of the concept of administrative and legal support of the legal regime of martial law is proposed as the activity of authorized subjects of public power in relation to the legal regulation of social relations, legal support for the implementation of the measures of the legal regime of martial law, regulated by the norms of administrative law, with the aim of protecting human rights and freedoms. defense of the state in case of armed aggression or threat of attack, danger to the state independence and territorial integrity of Ukraine. It has been established that the essence of the administrative and legal provision of the legal regime of martial law is the provision of conditions for achieving the goals of its introduction, as well as the provision of regulation, implementation, protection and protection of social relations in the conditions of martial law.

Розглянуто питання адміністративно-правового забезпечення правового режиму воєнного стану. Досліджено наукові погляди щодо таких правових категорій, як "правове забезпечення" та "адміністративно-правове забезпечення" у різних сферах суспільних відносин. Розглянуто поняття "адміністративно-правового забезпечення правового режиму воєнного стану" та встановлено його ключові ознаки, а саме: здійснюється спеціальними суб'єктами забезпечення зазначеного правового режиму, повноваження яких визначені законодавством; регулюється нормами адміністративного права; реалізовується за допомогою спеціального інструментарію (механізмів, заходів); діяльність суб'єктів публічного управління полягає у прийнятті законів, підзаконних нормативно-правових актів та їх реалізації. Запропоновано авторське визначення поняття адміністративно-правового забезпечення правового режиму воєнного стану як врегульовану нормами адміністративного права діяльність уповноважених суб'єктів публічної влади щодо правового регулювання суспільних відносин, правового забезпечення реалізації заходів правового режиму воєнного стану з метою захисту прав і свобод людини, оборони держави в разі збройної агресії чи загрози нападу, небезпеки державній незалежності та територіальній цілісності України. Встановлено, що сутністю адміністративно-правового забезпечення правового режиму воєнного стану є забезпечення умов для досягнення цілей запровадження такого правового режиму, а також забезпечення регулювання, реалізації, охорони і захисту суспільних відносин в умовах воєнного стану.
АДМІНІСТРАТИВНО-ПРАВОВЕ ЗАБЕЗПЕЧЕННЯ ПРАВОВОГО РЕЖИМУ ВОЄННОГО СТАНУ В УКРАЇНІ
Keywords: legal support; administrative-legal support; legal regime of martial law; administrative-legal support of the legal regime of martial law; signs of administrative-legal support of the legal regime of martial law; правове забезпечення; адміністративно-правове забезпечення; правовий режим воєнного стану; адміністративно-правове забезпечення правового режиму воєнного стану; ознаки адміністративно-правового забезпечення правового режиму воєнного стану